Abundance and diversity of butterfly in the Lombok Forest Park, Indonesia - Mohammad Liwa Ilhamdi; Agil Al Idrus; Didik Santoso; Gito Hadiprayitno; ‪Muhamad Syazali‬; Ismawan Hariyadi (Society for Indonesian Biodiversity, 2023)
Abstract. Ilhamdi ML, Al Idrus A, Santoso D, Hadiprayitno G, Syazali M, Hariyadi I. 2023. Abundance and diversity of butterfly in the Lombok Forest Park, Indonesia. Biodiversitas 24: 688-695. The lack of studies on butterflies on Lombok Island has prevented the biology and ecology of this insect group from being widely known. Further, the absence of data on insect communities impacts conservation management, especially that of the Lombok Island Forest Park. Insects can only be effectively managed for conservation by knowing their basic biology and ecology, yet almost nothing about the butterflies on Lombok Island has previously been quantified. This study aims to analyze the abundance and diversity of butterflies in the Forest Park of Lombok Island, Indonesia. The research was carried out from January to July 2022. Further, the samples were collected from three habitat types: waterways, forest middle lanes, and forest edge lanes. Butterfly data collection was carried out on the left and right of each line that became the transect. During this period, 1524 individuals from 42 butterfly species were collected. The most abundant species was Jamides celeno (Ra: 7.54%), while the species with the lowest abundance was Lampides boeticus (Ra: 0.26). The abundance of other species ranged from 0.45% to 6.95%. The results of the analysis show that the diversity of the butterflies in Lombok Island Forest Park is quite high in each of the habitat types surveyed. The data from this research can be used to design and implement conservation management, especially for butterflies.